Anatomy of a foetus of Balaenoptera borealis. - Schulte, Hermann von Wechlinger, 1876- (New York, 1916)
Extract from Memoirs of the American museum of natural history. New series, vol. 1, pt. VI. April, 1916. Plates accompanied by leaves with descriptive letterpress on both sides. Cover-title. Mode of access: Internet.